Two-axis position-based impedance control of a 2-DOF robotic finger / Khairunnisa Nasir - Nasir, Khairunnisa (2017)
In a previous work, a functional prototype of a custom three-fingered robotic hand has been successfully developed and verified for a grasping task using PID position control alone. However, it was very rigid in its motion which made it prone to damage when dealing with hard surface or when receiving external force from the environment. Thus, this study introduced the design of an impedance type of force control that considers the dynamic of the robotic rigorously to improve its current grasping capability by enabling the sense of touch which could produce softness like human hand to the robotic finger. As the preparation to enable the position-based impedance control development in two individual directions namely x-axis and z-axis, a calibration was done to the fabricated fingertip in both axes to produce a reference for converting the measured signal voltage (V) to the equivalent force value in Newton (N) for the two embedded force sensors inside the fingertip. The positionbased impedance control algorithm was designed by regulating the mechanical impedance of the robotic finger based on force measurements from the two embedded force sensors. The proposed position-based control was implemented sequentially with an existing PID position control through robot's kinematics. Initially, direct kinematics was derived for generating the targeted position within the finger's reachability range to the position-based impedance control. Inverse kinematics was also derived to convert the modified position resulted from the position-based impedance control into angle references for actuation of DC-micro motors located at each joint of the robotic finger. The proposed position-based impedance control and the developed kinematics were programmed using Matlab Simulink and tested in realtime experiments. The validation result has proven that the proposed position-based impedance control could modify the initial fingertip position according to the amount and direction of the applied external force, thus produced softness to the robotic finger.